MicroRNA-184 inhibits cell proliferation and metastasis in human colorectal cancer by directly targeting IGF-1R - Wu, Guannan (Oncol Lett, 2017)
Colorectal cancer is currently the third most common cancer in males and the second in females worldwide. In spite of marked progress having been achieved in surgical resection, radiotherapy and chemotherapy, the prognosis for patients with colorectal cancer remains poor. Previous studies have demonstrated that the abnormal expression of microRNAs contributed to human cancer carcinogenesis and progression, suggesting miRNAs as novel therapeutic targets in colorectal cancer. The aim of the present study was to investigate the expression, functions and underlying molecular mechanisms of microRNA-184 (miR-184) in colorectal cancer. The results identified that miR-184 was significantly downregulated in colorectal cancer tissues and cell lines. In vitro functional studies demonstrated that miR-184 significantly inhibited colorectal cancer cell proliferation, migration and invasion. Notably, insulin-like growth factor 1 receptor (IGF-1R) was identified as a direct target of miR-184 in colorectal cancer. Furthermore, the functions of IGF-1R small interfering RNA were similar to those induced by miR-184 in colorectal cancer, suggesting IGF-1R as a functional target of miR-184 in colorectal cancer. The results of the present study indicated that miR-184 may be a novel therapeutic strategy regimen of targeted therapy for colorectal cancer.